Initiation of adaptive feeding within 24 h after burn injury improves nutritional therapy for severely burned patients - Zhang, Yin; Dou, Yi; Yin, Zongqi; Gao, Min; Wu, Beiwen; Zhang, Qin (Frontiers in Nutrition, 2024)
Because of overly aggressive enteral nutrition immediately after burn injury has potential risks. Notably, adaptive feeding more closely resembles enteral nutrition. In this retrospective study, we analyzed factors influencing the selection of either modality, as well as the benefits of adaptive feeding. We sought to promote adaptive feeding as a precursor to initiating enteral nutrition.This retrospective study analyzed medical data from adult patients with extensive burns between January 2009 and December 2020. All patients had been admitted to the burn department within 24 hours after injury and had a burned area comprising >30% of total body surface area. Patients were divided into two groups: adaptive feeding and fasting. We examined the total burned area, full-thickness burned area, burn type, inhalation injury, start time of adaptive feeding, and start time of enteral nutrition. Outcome measures were 28-day mortality and hospital mortality. Univariate analysis revealed significant differences in burn type, percent of total body surface area (TBSA), full-thickness burned area, and inhalation injury between the adaptive feeding and fasting groups (all P<0.05). Linear regression analysis showed that full-thickness burned area and inhalation injury were the main factors influencing the start time of adaptive feeding in patients with severe burns (P<0.05). After propensity score matching analysis, the results showed that the start time of enteral nutrition was significantly earlier in the adaptive feeding group (P<0.01). However, overall mortality, 28-day mortality, and length of hospital stay did not significantly improve in the adaptive feeding group. The incidence of intolerance after enteral nutrition therapy did not significantly differ between groups.The results of the study showed that larger full-thickness burned areas and concomitant inhalation injury were the primary factors considered by physicians when selecting complete fasting for severely burned patients. Moreover, the results indicate that adaptive feeding improves nutritional therapy for severely burned patients by shortening the time between injury and initiation of enteral nutrition. Complete fasting due to concerns about extensive burned area and inhalation injuries does not reduce the incidence of enteral nutrition intolerance; instead, it delays the initiation of enteral nutrition.